Performance of waste tyre and palm oil fuel ash concrete - Nordin, Khairol Azhar (2013)
The performance of concrete mix in the presence of tyre particle and Palm Oil Fuel Ash (POFA) was investigated and compared with control mix. Tyre particle was used as sand replacement whereas POFA was used as a cement replacement. The proportion of the tyre particle varied in a percentage of 10%, 20% and 30% sand replacement while the proportion of POFA was fixed at 20%. Control specimen mixed with 0% POFA. And 1% of superplastisizer was added into concrete mix to improve its workability. The concrete was cured in water and was tested at 7, 14, 28 and 56 days. The tests conducted were slump test for workability and mechanical properties test (compressive, tensile, and flexural strength). The results showed that tyre particles decrease workability and the mechanical properties of concrete. The compressive strength and indirect tensile strength of concrete contain 20% POFA increases while its flexural strength decreases.